Pervasive sensing in chronic kidney disease - Han, Maggie; Williams, Schantel (Henry Stewart Talks, 2018)
Defining pervasive sensing, Example of use of wearable technology in medicine, Accuracy of wearable technologies, Physical activity’s role in improved health outcomes, Physical activity and sleep monitoring in ESRD patients, The effects of environment on physical activity levels, Role of environment in precision medicine